OVERVIEW OF FINANCIAL TECHNOLOGY (FINTECH) IN LOGISTICS: LITERATURE STUDY - Muhammad Arif Hernawan; Cecep Pahrudin; Muhammad Rifa Affiat; Siti Nurhayati (ABNUS Publisher, 2021)
The purpose of this study is to provide ideas in the existing literature from various sources that can be combined with the reality of existing scientific articles. The ideas and results of the research into this scientific article also provide an overview of the variables that can be used in further research such as data confidentiality, financial technology, logistics and government policy regulations. Of the three descriptions in the results and discussion above, there are three variables that can make future research materials or references, namely Financial technology that has been used with consumer confidentiality that is still not maximally maintained, secondly there is a government policy that clearly covers this financial technology so that it can be used. supervised by the government. Third, there are not many logistics companies that use financial technology as a means of payment to consumers, there are many obstacles, especially from management decisions and assistance that may be facilitated by the government with the existence of existing Financial Technology Institutions with cooperation. This qualitative research is still far from perfect, and only as a review material from researchers and as a contribution to the development of science, especially in the field of digital finance, and logistics in general. The research results of this article can provide thought benefits for science for those in need.